Psychology of the Digital Age : Humans Become Electric - Suler, John R. (Cambridge : Cambridge University Press, 2015)
Based on two decades of participant-observation field research in diverse online environments, this engaging book offers insights for improving lifestyles and enhancing wellbeing in the digital age. John R. Suler, a founder of the field of cyberpsychology, explains its fundamental principles across a wide variety of topics, including online identity management, disinhibition, communication via text and photographs, intimacy and misunderstandings in online relationships, conflicting attitudes toward social media, addiction, deviant behavior, virtual reality, artificial intelligence, and media overload. He provides a new framework, the'Eight Dimensions of Cyberpsychology Architecture', which researchers, students, and general readers interested in cyberpsychology can apply as a valuable tool for creating and understanding different digital realms. Psychology of the Digital Age focuses on the individual, shedding new light on our conscious as well as subconscious reactions to online experiences and our intrinsic human need to self-actualize.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).